Biblioteca escolar e a leitura School library and the reading p. 35-45 - Hillesheim, Araci Isaltina de Andrade; Fachin, Gleisy Regina Bóries (Revista ACB, 2005)
Relata-se a experiência em projetos de extensão apoiados pela UniversidadeFederal de Santa Catarina, com o objetivo de desenvolver atividades de incentivo àleitura em bibliotecas das escolas do ensino fundamental de Florianópolis/SC. Asatividades de incentivo à leitura são imprescindíveis em qualquer escola,principalmente no ensino fundamental, onde estas atividades deveriam serrealizadas com a colaboração mútua entre professores e a biblioteca. Destaca-seque a presença do bibliotecário passou a ser valorizada e fundamental para odesenvolvimento de atividades de incentivo à leitura e outras inerentes à bibliotecaescolar. Abstract: Presents the work developed within the community project sponsored by theFederal University of Santa Catarina – UFSC, with objetive to incentive readingsby pupils of the elementary school in Florianópolis /SC. The activities regardingreading are essential to the school environment, in particular in the elementarylevel. At this level it is important the integrated action of librarians and teachers.The present work brought a valorization of the librarian as an active element withinthe learning process, as well as an other activities related the school library. Keywords: School library; Reading incentive; Habit of reading; School librarian.